Combination of CDX2 expression and T stage improves prognostic prediction of colorectal cancer. Issue 5 (May 2019) - Xu, Weimin; Zhu, Yilian; Shen, Wei; Ding, Wenjun; Wu, Tingyu; Guo, Yuegui; Chen, Xiaobing; Zhou, Mingxia; Chen, Yingwei; Cui, Long; Du, Peng
Objective: Prognostic prediction of colorectal cancer (CRC) remains challenging because of its heterogeneity. Aberrant expression of caudal-type homeobox transcription factor 2 (CDX2) is strongly correlated with the prognosis of CRC. Methods: Tissue samples of patients with CRC who underwent surgery in Xinhua Hospital (Shanghai, China) from January 2010 to January 2013 were collected. CDX2 expression was semiquantitatively evaluated via immunohistochemistry. Results: In total, 138 patients were enrolled in this study from a prospectively maintained institutional cancer database. The median follow-up duration was 57.5 months (interquartile range, 17.0–71.0 months). In the Cox proportional hazards model, low CDX2 expression combined with stage T4 CRC was significantly the worst prognostic factor for disease-free survival (hazard ratio = 7.020, 95% confidence interval = 3.922–12.564) and overall survival (hazard ratio = 5.176, 95% CI = 3.237–10.091). In the Kaplan–Meier survival analysis, patients with low CDX2 expression and stage T4 CRC showed significantly worse disease-free survival and overall survival than those with low CDX2 expression alone. Conclusion: CDX2 expression combined with the T stage was more accurate for predicting the prognosis of CRC. Determining the prognosis of CRC using more than one variable is valuable in developing appropriate treatment and follow-up strategies.